Hamlet Toponymy in Cadasari-Pandeglang Sub-district as an Effort to Increase Sundanese Language Preservation Literacy - Yana, Asep; Maelani, Puspita (KnE Social Sciences, 2024)
Indonesia occupies the second position as the country with the most regional languages in the world. This is a great capital considering Indonesia’s position which is increasingly taken into account in the eyes of the world. In rural areas, local languages still occupy an important position because even now there are many people who do not know Indonesian well, especially in the outermost, deepest, and least developed regions. Thus, local languages are still an effective means of communication. This research was made as an effort to increase literacy in the preservation of regional languages, namely Sundanese. This research aims to improve literacy and preservation of Sundanese language in Pandeglang district, Banten Province by using language preservation strategies through digital toponymy studies. The method used in this research is qualitative with a descriptive approach. Data were collected using questionnaire techniques, interviews, and direct observation in the field. The location of this research is Cadasari Sub-district, Pandeglang Regency, Banten. The respondents of this research, namely the people in Cadasari sub-district, were selected based on age, especially those who knew the history of naming the names of hamlets/village. The informants of this research are community leaders in Pandeglang tribe. The results showed that each hamlet has a unique name origin that can be traced to its philosophy. The results prove that to map the level of literacy, toponymy studies and preservation of Pandeglang Sundanese language, there are hamlet names that have been collected based on direct observation tracing in the field. The data obtained are five names of hamlets: 1. Kadu Kalapa village, 2. Pasir Haur village, 3. Kadu Sampir village, and 4. Cikentrung village. In addition, this research can help the government to determine policies for overcoming literacy problems, especially in Cadasari Sub-district, Pandeglang Regency Banten. Keywords: toponymy, literacy, language preservation